El análisis financiero como instrumento para la toma de decisiones gerenciales en la Ferretería Vilca E.I.R.L. año 2024 - Vela Ferry, Mercedez del Rosario (2025)
The different changes that occur in financial analysis are oriented to the use of the instrument for correct decision making. The current thesis carries out an investigation of Financial Analysis is an instrument that contributes to managerial decision making at Ferretería Vilca E.I.R.L. Year 2024. For this purpose, this Quantitative research, Correlational level and Non Experimental design was carried out. The research concludes with Financial Analysis is an instrument that contributes to managerial decision making at Ferretería Vilca E.I.R.L. Year 2024, demonstrated in Table 1. Likewise, it has been verified that the specific hypothesis 1. Vertical Financial Analysis is an instrument that contributes to managerial decision making at Ferretería Vilca E.I.R.L. Year 2024. Table 3. On the other hand, in the specific hypothesis 2. The Horizontal Financial Analysis is an instrument that contributes to managerial decision-making at Ferretería Vilca E.I.R.L. Year 2024. in Table 6. Finally, the specific hypothesis 3. The Financial Analysis of ratios is an instrument that contributes to managerial decision-making at Ferretería Vilca E.I.R.L. Year 2024 obtained in Table 12.